A non-flammable electrolyte for lithium battery and its application
By introducing low-coordinate co-solvents and additives into the lithium battery electrolyte, an anion-rich ion-solvent complex structure is formed, which solves the problems of poor safety and insufficient compatibility of the existing lithium battery electrolyte, and achieves high safety and excellent electrochemical performance.
Patent Information
- Application Number
- CN202211119166.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-09-13
AI Technical Summary
The existing lithium battery electrolyte has poor safety, is flammable and explosive, and is incompatible with the negative electrode material, resulting in insufficient thermal stability and cycle life of the battery.
An electrolyte including organic solvents, lithium salts and additives is used to introduce low-coordinate co-solvents into phosphate solvents to form an anion-rich ion-solvent complex structure, improve the LUMO energy level and reduction stability of the electrolyte, enhance compatibility with the negative electrode, and improve the composition structure of the SEI film through additives.
It realizes high safety, excellent electrochemical stability and excellent circulation performance of lithium battery electrolyte, while maintaining the non-combust properties of phosphate solvents, and is suitable for large-scale production.
Smart Images

Figure CN115312856B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium battery electrolyte, and in particular to a lithium battery non-combustible electrolyte and application thereof. Background Art
[0002] Lithium batteries are currently the most advanced type of chemical power technology, with outstanding advantages such as high operating voltage, high energy density and power density, and long cycle life. They have currently occupied the main market for power sources for portable electronic products and electric vehicles, and are gradually penetrating into the field of power storage.
[0003] The poor intrinsic safety of lithium batteries is mainly due to the low flash point and boiling point of commercial carbonate electrolytes, which are flammable and explosive and have extremely poor safety performance. In addition, in pursuit of high energy density, batteries all use high-capacity electrode materials (high-nickel ternary positive electrode, high-voltage lithium cobalt oxide positive electrode, silicon-carbon negative electrode, lithium metal negative electrode, etc.). These materials have poor thermal stability, which further aggravates the safety risks of batteries.
[0004] Phosphate compounds have the characteristics of low viscosity, high dielectric constant, low cost and non-flammability. However, phosphate electrolytes are completely incompatible with commonly used battery negative electrodes (graphite negative electrodes or lithium metal negative electrodes, silicon-carbon negative electrodes). Although predecessors have preliminarily solved the compatibility problem with the negative electrode by designing high molar ratio (solute / solvent) phosphate electrolytes, high molar ratio electrolytes have high viscosity and high cost, and are still difficult to apply on a large scale. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a non-flammable electrolyte for lithium batteries, which still maintains the non-flammable properties of phosphate solvents, effectively ensures the safety of the battery, and at the same time exhibits excellent electrochemical stability and excellent cycle performance in application.
[0006] The present invention is achieved in that:
[0007] The present invention provides an organic solvent, a lithium salt and an additive. The organic solvent includes a solvent A and a solvent B. The solvent A is a phosphate solvent having a strong coordination ability with lithium ions, the solvent B is a co-solvent having a weak coordination ability with lithium ions, and the additive is a film-forming additive.
[0008] Non-flammable phosphate solvents have strong coordination ability with lithium ions, and will form a four-coordination structure without anion participation in the first solvation shell of lithium ions. In this structure, since lithium ions need to obtain electrons for desolvation, the electron cloud density around the solvent molecules coordinated with them decreases, and the solvent molecules will attract electrons around the negative electrode and be reduced, resulting in the so-called co-embedding phenomenon. The present invention introduces a low-coordination number solvent into a high-coordination number phosphate solvent, so that the number of coordinations in the first solvation shell of lithium ions is not full, thereby introducing anions into the solvation structure of lithium ions, forming an anion-rich ion-solvent complex structure, effectively improving the LUMO energy level and reduction stability of the electrolyte, and achieving compatibility with a graphite negative electrode (or a lithium metal negative electrode, a silicon-carbon negative electrode) at a low lithium salt concentration.
[0009] At the same time, the added additives can participate in the formation of the SEI film on the surface of the negative electrode, improve its composition structure, and further enhance the cycle stability of the negative electrode. The electrolyte still maintains the non-flammable properties of phosphate ester solvents, effectively ensuring the safety of the battery.
[0010] Furthermore, the content of solvent A accounts for 30% to 70% of the total mass of the electrolyte, the content of solvent B accounts for 20% to 60% of the total mass of the electrolyte, the content of lithium salt accounts for 5% to 20% of the total mass of the electrolyte, and the content of additives accounts for 0.1% to 5% of the total mass of the electrolyte.
[0011] Furthermore, the solvent A is one or more of dimethyl methylphosphonate, diethyl methylphosphonate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tripentyl phosphate, trihexyl phosphate, trioctyl phosphate, triphenyl phosphate, tricresyl phosphate, tris(1,3-dichloropropyl) phosphate, tris(2-chloroethyl) phosphate, and tris(2,2,2-trifluoroethyl) phosphate.
[0012] Furthermore, the solvent B is one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl difluoroacetate, ethyl difluorochloroacetate, ethyl difluorobromoacetate, and ethyl 2-nitroacetate.
[0013] Furthermore, the lithium salt is one or more of lithium hexafluorophosphate, lithium dioxalatoborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium perchlorate, lithium difluorooxalatoborate, lithium nitrate and lithium trifluoromethanesulfonate.
[0014] Furthermore, the additive is one or more of fluoroethylene carbonate, 1,2-difluoroethylene carbonate, vinyl sulfate, 4-methyl vinyl sulfate, 4-ethyl vinyl sulfate, 1,3-dioxol-2-one, lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate borate), and lithium difluorooxalate borate.
[0015] The present invention also provides a high-safety lithium battery, comprising a positive electrode, a negative electrode and the non-flammable electrolyte.
[0016] Furthermore, the positive electrode active material is LiFePO 4 、LiCoO 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.5~ 0.9 Co 0.05~0.2 Mn 0.05~0.3 O 2 The negative electrode is one or more of graphite, lithium metal, and silicon carbon.
[0017] The present invention has the following beneficial effects:
[0018] 1. The lithium battery electrolyte prepared by the present invention can achieve compatibility between phosphate electrolyte and negative electrode at low concentration by regulating the solvation structure, which greatly improves the safety of the battery while ensuring the excellent electrochemical performance of the battery;
[0019] 2. The lithium battery electrolyte prepared by the present invention can improve the composition of the SEI film on the surface of the negative electrode, which is beneficial to improving the cycle stability of the negative electrode;
[0020] 3. The lithium battery electrolyte prepared by the present invention has a simple preparation process, low cost, and can be used for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The first week charge and discharge curve of the graphite half-cell using the electrolyte of Comparative Example 1 in the present invention (current density 50 mA g -1 );
[0023] Figure 2The first week charge and discharge curves (current density 50 mA g) of the graphite half-cell using the electrolyte of Examples 1-4 of the present invention -1 );
[0024] Figure 3 The capacity-cycle curves of the graphite half-cells using the electrolytes of Examples 4 and 5 of the present invention (cycle current density 100 mA g -1 );
[0025] Figure 4 The ignition test results of the glass fiber separators made of the electrolytes of Comparative Example 2 and Example 5 in the present invention;
[0026] Figure 5 Li||LiCoO in the electrolyte of Example 6 of the present invention 2 Capacity-cycle number and Coulomb efficiency-cycle number curves of lithium batteries (cycle current density 100mA g -1 );
[0027] Figure 6 Li||LiFePO in the electrolyte of Example 7 of the present invention 4 Capacity-cycle number and coulombic efficiency-cycle number curves of lithium batteries (cycle current density 170mA g -1 );
[0028] Figure 7 Li||LiNi in the electrolyte of Example 8 used in the present invention 0.8 Co 0.15 Al 0.05 O 2 Capacity-cycle number and Coulomb efficiency-cycle number curves of lithium batteries (cycle current density 100mA g -1 );
[0029] Figure 8 The soft pack battery (positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O 2 , the negative electrode is graphite) under 0.5C cycle capacity-cycle number and coulomb efficiency-cycle number curve;
[0030] Fig. 9 The soft pack battery (positive electrode LiNi 0.8 Co 0.1 Mn 0.1 O 2 , the negative electrode is silicon carbon) under 0.5C cycle capacity-cycle number and coulomb efficiency-cycle number curve;
[0031] Fig.10 The puncture test results of the soft-pack batteries using the electrolytes of Comparative Example 2 and Example 5 of the present invention are shown. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] In an argon atmosphere glove box with an oxygen content and a moisture content both below 0.1 ppm, lithium hexafluorophosphate was dissolved in a mixed solvent of tris(2,2,2-trifluoroethyl)phosphate / 2,2,2-trifluoroethyl methyl carbonate in a mass ratio of 4:1, wherein the mass of lithium hexafluorophosphate was 0.76 g and the total mass of the solvent was 7.5 g, to obtain 5 mL
[0035] The electrolyte of Example 1 was magnetically stirred for 1 hour, sealed and placed in a glove box to avoid light for later use.
[0036] Example 2
[0037] Different from Example 1, the mass ratio of the tris(2,2,2-trifluoroethyl)phosphate / 2,2,2-trifluoroethyl methyl carbonate mixed solvent is 7:3.
[0038] Example 3
[0039] Different from Example 1, the mass ratio of the tris(2,2,2-trifluoroethyl)phosphate / 2,2,2-trifluoroethyl methyl carbonate mixed solvent is 3:2.
[0040] Example 4
[0041] Different from Example 1, the mass ratio of the tris(2,2,2-trifluoroethyl)phosphate / 2,2,2-trifluoroethyl methyl carbonate mixed solvent is 1:1.
[0042] Example 5
[0043] Different from Example 1, the mass ratio of tris(2,2,2-trifluoroethyl)phosphate / 2,2,2-trifluoroethylmethyl carbonate mixed solvent is 1:1, and functional additives are added: 0.4 g fluoroethylene carbonate (FEC) and 0.072 g LiODFB.
[0044] Example 6
[0045] In an argon atmosphere glove box with an oxygen content and a moisture content both lower than 0.1 ppm, lithium bis(trifluoromethanesulfonyl)imide was dissolved in a tris(2,2,2-trifluoroethyl)phosphate / dimethyl carbonate mixed solvent in a mass ratio of 2:3, wherein the mass of lithium bis(trifluoromethanesulfonyl)imide was 0.94 g and the total mass of the solvent was 7.5 g. 0.4 g of fluoroethylene carbonate (FEC) and 0.072 g of LiODFB functional additives were added to obtain 5 mL of the electrolyte of Example 6, which was magnetically stirred for 1 hour and sealed in a glove box to protect from light for standby use.
[0046] Example 7
[0047] In an argon atmosphere glove box with an oxygen content and a moisture content both lower than 0.1 ppm, lithium bis(fluorosulfonyl)imide was dissolved in a mixed solvent of trimethyl phosphate / diethyl carbonate in a mass ratio of 3:7, wherein the mass of lithium bis(fluorosulfonyl)imide was 0.94 g and the total mass of the solvent was 5.5 g. 0.12 g of 1,2-difluoroethylene carbonate was added as a functional additive to obtain 5 mL of the electrolyte of Example 7. The electrolyte was magnetically stirred for 1 hour and sealed in a glove box to protect from light for later use.
[0048] Example 8
[0049] In an argon atmosphere glove box with an oxygen content and a moisture content both lower than 0.1 ppm, lithium perchlorate was dissolved in a 1:1 triethyl phosphate / ethyl methyl carbonate mixed solvent, wherein the mass of lithium perchlorate was 0.55 g and the total mass of the solvent was 6 g. 0.05 g of a functional additive of vinyl sulfate was added to obtain 5 mL of the electrolyte of Example 8. The electrolyte was magnetically stirred for 1 hour and sealed in a glove box to protect from light for later use.
[0050] Comparative Example 1
[0051] Preparation of a single phosphate solvent lithium battery electrolyte: In an argon atmosphere glove box with an oxygen content and a moisture content both lower than 0.1 ppm, lithium hexafluorophosphate was dissolved in a solvent tri(2,2,2-trifluoroethyl) phosphate, wherein the mass of lithium hexafluorophosphate was 0.76 g and the total mass of the solvent was 8 g, to obtain 5 mL of comparative example 1 electrolyte, which was magnetically stirred for 1 hour and sealed in a glove box to be protected from light for later use.
[0052] Comparative Example 2
[0053] Preparation of common commercial lithium battery electrolyte: In an argon atmosphere glove box with oxygen content and moisture content both lower than 0.1 ppm, lithium hexafluorophosphate was dissolved in a 1:1 mixed solvent of ethylene carbonate / ethyl methyl carbonate, wherein the mass of lithium hexafluorophosphate was 0.76 g and the total mass of the solvent was 6 g, to obtain 5 mL of comparative example 2 electrolyte, magnetically stirred for 1 hour, and sealed and placed in a glove box to protect from light for later use.
[0054] The electrochemical performance of the electrolyte prepared above was tested:
[0055] The processes involved in making button batteries and soft-pack batteries are as follows:
[0056] Button battery: The positive electrode is made of LiFePO 4 Powder (or LiCoO 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.5~ 0.9 Co 0.05~0.2 Mn 0.05~0.3 O 2 ), acetylene black conductive carbon (AB) and PVDF binder, active material: AB: PVDF = 90:5:5. 4 The powder and AB were ground in a mortar for 20 minutes according to the proportion to be evenly mixed, the evenly mixed powder was mixed with PVDF (5% NMP solution), placed in a micro ball mill and stirred for 20 minutes to obtain a uniform slurry, the slurry was evenly coated on aluminum foil, vacuum dried in an oven at 80°C for 10 hours, and a positive electrode sheet with a diameter of 12 mm was pressed out, which was weighed and set aside for use;
[0057] The negative electrode sheet is composed of artificial graphite (or silicon carbon), Super P conductive carbon, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) binder, and the active material is Super P: SBR: CMC = 85: 6: 4.5: 4.5. The artificial graphite powder and Super P conductive carbon are ground and mixed evenly for 20 minutes in proportion, and the mixed artificial graphite and Super P conductive carbon are mixed with SBR (49.5% aqueous solution) and CMC (2% aqueous solution), and stirred on a micro ball mill for 15 minutes to obtain a uniform slurry, and the slurry is evenly coated on the copper foil, vacuum dried in an oven at 80°C for 5 hours, and a negative electrode sheet with a diameter of 12 mm is punched out with a gun press, and weighed for standby use.
[0058] Soft pack battery: the positive electrode is made of LiNi 0.8 Co 0.1 Mn 0.1 O 2The active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 97:1.5:1.5, and then coated on aluminum foil, dried, and cold pressed. The negative electrode sheet is made of graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) in a deionized water solvent system at a mass ratio of 96:1:1.5:1.5. After being fully stirred and mixed, it is coated on copper foil, dried, and cold pressed to obtain a negative electrode sheet. The positive electrode sheet, isolation film, and negative electrode sheet are stacked in sequence and wound in the same direction to obtain a bare battery cell, which is packaged with aluminum-plastic film. The battery after liquid injection is packaged, shelved, formed, aged, secondary packaged, and capacity divided to obtain a soft-pack lithium battery. The surface density of the positive and negative electrodes is 21.2 mg cm -2 and 36mgcm -2 , the injection volume is 12g.
[0059] The results are analyzed as follows:
[0060] See Figure 1 The reversible specific capacity of the battery using the electrolyte of Comparative Example 1 is only 20 mAh g -1 , which indicates that conventional low-concentration phosphate electrolytes are not compatible with graphite;
[0061] Figure 2 The first week charge and discharge curves of batteries with different FEMC contents of low-coordinating solvents. It can be seen that with the increase of FEMC content, the reversible capacity of the battery gradually increases. When the FEMC mass fraction reaches 40%, a platform for lithium ion deintercalation in graphite appears. When the FEMC volume fraction is further increased, there is no obvious difference in the reversible specific capacity of the battery.
[0062] Figure 3 The figures are the cycle performance test results of the batteries of the electrolytes of Examples 4 and 5. After adding 0.4 g of fluoroethylene carbonate (FEC) and 0.072 g of LiODFB as functional additives, the rate performance and cycle performance of the batteries are significantly enhanced.
[0063] Figure 4 The ignition test results of the glass fiber separators soaked in Comparative Example 2 and Example 5 show that the separator of Comparative Example 2 ignites quickly, while the separator of Example 5 is completely non-flammable, showing a good flame retardant effect.
[0064] Figure 5 The electrolyte of Example 6 is Li||LiCoO 2 The cycle performance test results of lithium batteries show that the capacity retention rate is still over 80% after 350 cycles;
[0065] Figure 6The electrolyte of Example 7 is Li||LiFePO 4 The test results of the cycle performance of the lithium battery show that the electrolyte of Example 7 exhibits excellent compatibility with the lithium iron phosphate positive electrode;
[0066] Figure 7 The electrolyte of Example 8 is Li||LiNi 0.8 Co 0.15 Al 0.05 O 2 The cycling performance test results of lithium batteries provide a cycle retention rate of nearly 80% in 200 cycles, showing excellent cycling performance;
[0067] Figure 8 and Fig. 9 The results of the cycle performance test of the soft-pack battery (the negative electrode is graphite and silicon carbon, respectively) using the electrolyte of Example 5 at a current density of 0.5C (2.5A), wherein the soft-pack battery using the graphite negative electrode has a capacity retention rate of 82.7% after 250 cycles, and the soft-pack battery using the silicon carbon negative electrode has a capacity retention rate of nearly 90% after 100 cycles, both showing excellent electrochemical stability;
[0068] Fig.10 This is a needle puncture test of soft-pack batteries using the electrolytes of Comparative Example 2 and Example 5. The soft-pack battery using the electrolyte of Comparative Example 2 quickly caught fire and exploded, while the battery using the electrolyte of Example 5 was only slightly bloated, showing excellent safety.
[0069] In summary, the electrolyte of the present invention constructs a composite system of high-coordination number phosphate-low-coordination number co-solvent. By introducing a low-coordination number solvent into a phosphate solvent, anions can be introduced into the solvation sheath of lithium ions, forming an anion-induced ion-solvent complex solvation structure with stronger reduction stability, thereby improving the compatibility of the electrolyte with the negative electrode. The added functional additives can also participate in the formation of the SEI film on the surface of the negative electrode, improve its composition structure, and further enhance the cycle stability of the negative electrode.
[0070] The electrolyte used in the battery exhibits excellent electrochemical stability and excellent cycle performance. At the same time, the electrolyte still maintains the non-flammable property of the phosphate solvent, effectively ensuring the safety of the battery. The electrolyte of the present invention is simple in design, low in cost, and easy to scale up for use.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A non-flammable electrolyte for lithium batteries, comprising an organic solvent, a lithium salt and an additive, characterized in that: The organic solvent includes solvent A and solvent B, wherein solvent A is a phosphate ester solvent having a strong coordination ability with lithium ions, and solvent B is a co-solvent having a weak coordination ability with lithium ions, and the additive is a film-forming additive; The solvent A is tris(2,2,2-trifluoroethyl)phosphate; The solvent B is 2,2,2-trifluoroethyl methyl carbonate; The mass ratio of the solvent A to the solvent B is 3:2; The lithium salt is lithium hexafluorophosphate, the mass of lithium hexafluorophosphate is 0.76 g, and the total mass of the organic solvent is 7.5 g.
2. The non-flammable electrolyte for lithium batteries according to claim 1, characterized in that: The additive is one or more of fluoroethylene carbonate and lithium difluorooxalate borate.
3. A high-safety lithium battery, characterized in that: It comprises a positive electrode, a negative electrode and the non-flammable electrolyte of a lithium battery as claimed in any one of claims 1 to 2.
4. The high-safety lithium battery according to claim 3, characterized in that: The positive electrode active material is LiFePO4, LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.5~0.9 Co 0.05~0.2 Mn 0.05~0.3 The negative electrode is one or more of graphite, lithium metal, and silicon carbon.
Citation Information
Patent Citations
Inflaming retarding phosphorus-based electrolyte for lithium metal battery and lithium metal battery
CN109860705A